2012
DOI: 10.5402/2012/962014
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment in Nail Salons: An Indoor Air Approach

Abstract: Due to the complexity of the nail salon work environment, traditional approaches to exposure assessment in this context tend to mischaracterize potential hazards as nuisances. For this investigation, a workable “indoor air” approach was devised to characterize potential hazards and ventilation in Boston, Massachusetts area nail salons which are primarily owned and staffed by Vietnamese immigrants. A community-university partnership project recruited salons to participate in a short audit which included carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Among nail salons, the program focused on distributing Material Safety Datasheets, training community health workers to recognize work-related health issues for nail salon workers, and promoting the use of National Institute of Occupational Safety Health-approved N95 masks, but we did not find any published research evaluation of the effectiveness of the outreach. There were, however, some baseline descriptive assessments conducted as part of the program [Roelofs et al, 2008;Roelofs and Do, 2012]. This model program was one of the first to address worker health and safety in this large, underserved immigrant worker population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among nail salons, the program focused on distributing Material Safety Datasheets, training community health workers to recognize work-related health issues for nail salon workers, and promoting the use of National Institute of Occupational Safety Health-approved N95 masks, but we did not find any published research evaluation of the effectiveness of the outreach. There were, however, some baseline descriptive assessments conducted as part of the program [Roelofs et al, 2008;Roelofs and Do, 2012]. This model program was one of the first to address worker health and safety in this large, underserved immigrant worker population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing body burden levels of dibutyl phthalate show high levels from workplace exposure [Kwapniewski et al, 2008] with levels over twice as high as the general population [Hines et al, 2009], and have linked this compound to reproductive problems [Swan, 2006[Swan, , 2008. Findings from descriptive studies report that many nail salon workers are reporting health effects commonly associated with overexposure to solvents [Quach et al, 2008;Roelofs et al, 2008;Roelofs and Do, 2012], including neuropsychological symptoms due to low level exposure to neurotoxicants [LoSasso et al, 2001;LoSasso et al, 2002]. Findings from descriptive studies report that many nail salon workers are reporting health effects commonly associated with overexposure to solvents [Quach et al, 2008;Roelofs et al, 2008;Roelofs and Do, 2012], including neuropsychological symptoms due to low level exposure to neurotoxicants [LoSasso et al, 2001;LoSasso et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these VOCs have known or suspected adverse effects, including: irritation to eye, skin and nose; damage to the respiratory system, liver and kidney; reproductive effects; and breast cancer. Several studies have indicated potentially harmful exposure levels (Alaves et al 2013; Quach et al 2011; Quach et al 2008; Quach et al 2013; Roelofs et al 2008; Roelofs and Do 2012; Tsigonia et al 2010), e.g., formaldehyde levels exceeded the National Institute for Occupational Safety and Health recommended exposure limits (NIOSH RELs) in 58% of samples collected in a California study (Alaves et al 2013). Adverse health effects observed among NSTs include asthma, dermatitis, and neurological symptoms (Quach et al 2014; Roelofs et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…several authors (Mendicino, 2000;Maurer et al, 2001;Anderson and Anderson, 2003;Greenberg et al, 2003;Hathaway and Proctor, 2004;Agyeman and Himmelberger, 2009;Halverson, 2011;Battersby, 2011;Roelofs and Do, 2012;ATSDR, 2015) who found the components of dry erase ink to be irritants.…”
mentioning
confidence: 99%